Arc-length Algorithm Efficiency in the Analysis of Thermally Loaded Multilayered Shells - SABIK, Agnieszka; KREJA, Ireneusz (Engineering Transactions, 2015)
This paper concerns the efficiency study of the arc-length algorithm in the geometrically non-linear analysis of thermally loaded multilayered shells. The thermal loading is considered as the one-way thermo-mechanical coupling effect. Two implementations of the arc-length method are examined: the path-following technique available in NX-Nastran and the Riks-Wempner-Ramm algorithm adopted in the authors’ computer code SHLTH. It is shown that the appropriate unloading condition in each step of the analysis plays the crucial role in obtaining a proper solution. The algorithm offered in NX-Nastran tends to fail, whereas the authors’ code enables to find the solution in required temperature range.